2021
DOI: 10.26803/ijlter.20.3.8
|View full text |Cite
|
Sign up to set email alerts
|

What do Malaysian ESL Teachers Think About Flipped Classroom?

Abstract: Student-centred teaching and learning methods are favoured for promoting active and collaborative learning. In the flipped classroom approach, student-centred teaching and learning are the focus in the learning process. The approach has been gaining attention from educators at all levels worldwide. The present study was aimed at exploring Malaysian primary ESL (English as a Second Language) teachers’ perceptions of the implementation of flipped classroom. The study used the mixed method design, a Likert-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…While the assimilation learning processes occurred in flipped classroom dynamics requested the learners to formulate various critical inquiries and explain the complex learning conceptions clearly to other learning community members. Kiang and Yunus (2021) contended that a high-quality flipped classroom approach should comprise analytical, critical, reasoning, and self-reliant skills unless the ongoing second language learning processes will be debilitating for all learning community members.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While the assimilation learning processes occurred in flipped classroom dynamics requested the learners to formulate various critical inquiries and explain the complex learning conceptions clearly to other learning community members. Kiang and Yunus (2021) contended that a high-quality flipped classroom approach should comprise analytical, critical, reasoning, and self-reliant skills unless the ongoing second language learning processes will be debilitating for all learning community members.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This rewarding learning benefit is more likely to happen since learners have long-term independent learning periods where they can understand those posted learning materials to have more mutual discussions with their learning counterparts and teachers. Kiang and Yunus (2021) unveiled that many EFL learners not only become more knowledgeable but also well-prepared with the supervision of flipped classroom learning approach as they have fully comprehended the particular subject-specific matters assigned by their teachers to be further discussed in the physical learning circumstances. McNally et al (2017) suggested that EFL teachers willing to incorporate this student-centered learning approach in their classroom vicinities should keep four fundamental principles in mind.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers were worried about how all students will be able to have the required handson experience with the tool that would be used in the flipped classroom (Kiang & Yunus, 2021), and they were especially concerned about children who do not have access to computers at home. The teachers were concerned about the irregularity of the internet connection (Ramadhanty & Puspitaloka, 2020), the exorbitantly expensive cost of the necessary equipment (Magaña et al, 2022), and the significant time investment needed to painstakingly prepare the lectures (Fulgueras & Bautista, 2020).…”
Section: Theme 3 Worries and Anxietiesmentioning
confidence: 99%
“…In contrast, Flipped classroom model, students watch video lectures at home, learn other materials, and then actively participate in during classroom (Kiang & Yunus, 2021). Different from conventional lecturing that only focuses on a single source of the textbook, in this learning, the knowledge, skills, attitudes, and the material source are gathered from many sources available online (self-learning materials).…”
Section: F What Are Students' Perceptions Of Flippedmentioning
confidence: 99%